AHP-based risk identification risk assessment and risk allocation approach for the micromobility sector - Yemlihalıoğlu, Emir. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2022., 2022)
In today’s world, where the micromobility sector, which is one of the most important sub-headings of the sharing economy model, in which people pay for the products and services they need for a short time, without owning them, is rapidly becoming widespread, many people and institutions are directly and indirectly affected by this situation. To minimize the negative effects and take the necessary precautions, the current situation should be revealed and the risks that may arise should be determined. After examining the sharing economy and risk allocation concepts, first of all, the risks arising from the micromobility sector were determined in this study. Afterward, the AHP method, which is one of the multi-criteria decision-making methods, was explained and the surveys prepared were evaluated by the experts, the determined risks were distributed among the alternatives, and the opportunity to guide and share responsibility for the applications to be made after that was provided. Based on this study, it was easier to determine the main topics for future research.
Keywords: Transportation -- Research.; Ridesharing -- Management.; Electric vehicles.